2022
DOI: 10.1002/dug2.12028
|View full text |Cite
|
Sign up to set email alerts
|

Potential triggers for large earthquakes in open‐pit mines: A case study from Kuzbass, Siberia

Abstract: The extraction and movement of rock during mining operations is considered a possible trigger for slip along the fault. In this study, possible anthropogenic causes were analyzed for triggering the earthquake with the local magnitude of M L = 6.1 (at a depth of 4 km just beneath the quarry), in the vicinity of the large coal open-pit mine in Russia. This event was the largest earthquake associated with a quarry (an open pit). A sufficiently deep occurrence of the source testified that seismic vibrations were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The regularity of rapid aftershocks varies in space and time. Kocharyan et al (2022) analyzed one of the largest earthquakes initiated by mining operations with a magnitude of M = 5.5 (M L = 6.1) at a depth of 4 km just beneath the quarry, namely, the Bachat earthquake, which occurred on June 18, 2013 in the vicinity of the large coal open-pit mine in Kuzbass in Russia. They calculated the increments of normal and shear stresses at fault planes with several dip angles at hypocenter depths of the Bachat earthquake and showed that the stress state under long-term rock excavation approached closer to the ultimate Coulomb strength.…”
Section: Research On the Triggering Mechanism Caused By Explosionsmentioning
confidence: 99%
“…The regularity of rapid aftershocks varies in space and time. Kocharyan et al (2022) analyzed one of the largest earthquakes initiated by mining operations with a magnitude of M = 5.5 (M L = 6.1) at a depth of 4 km just beneath the quarry, namely, the Bachat earthquake, which occurred on June 18, 2013 in the vicinity of the large coal open-pit mine in Kuzbass in Russia. They calculated the increments of normal and shear stresses at fault planes with several dip angles at hypocenter depths of the Bachat earthquake and showed that the stress state under long-term rock excavation approached closer to the ultimate Coulomb strength.…”
Section: Research On the Triggering Mechanism Caused By Explosionsmentioning
confidence: 99%
“…Compared with other heating methods, geothermal heating has the advantages of environmental protection, stability, being economical, and having significant energy-saving effects. China has enormous potential for deep geothermal energy resources, so exploring the use of deep geothermal energy is of great significance [4][5][6]. In the future, the development of geothermal energy will tend to develop and utilize deep geothermal energy and high-temperature magma energy and gradually focus on the comprehensive utilization of geothermal heating, refrigeration, hot springs, and bathhouses [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%